Dysfunction of Mesenchymal Stem Cells Isolated from Metabolic Syndrome and Type 2 Diabetic Patients as Result of Oxidative Stress and Autophagy may Limit Their Potential Therapeutic Use - Kornicka, Katarzyna (Stem Cell Rev, 2018)
Mesenchymal stem cells (MSC) have become a promising tool for therapeutic intervention. Their unique features, including self-renewal, multipotency and immunomodulatory properties draw the worldwide attention of researchers and physicians with respect to their application in disease treatment. However, the environment (so-called niche) from which MSCs are isolated may determine their usefulness. Many studies indicated the involvement of MSCs in ageing and disease. In this review, we have focused on how type 2 diabetes (T2D) and metabolic syndrome (MS) affect MSC properties, and thus limit their therapeutic potential. Herein, we mainly focus on apoptosis, autophagy and mitochondria deterioration processes that indirectly affect MSC fate. Based on the data presented, special attention should be paid when considering autologous MSC therapy in T2D or MS treatments, as their therapeutic potential may be restricted.